Diversifikasi Produk Olahan Ikan Laosan sebagai Upaya Meningkatkan Daya Saing UMKM di Desa Gumeng, Kecamatan Bungah, Kabupaten Gresik - Dia Puspitasari; Jenry Munson Rawung; Devi Ratih Cyntiasari; Amalia Jaudah; Bery Dava Saputra (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2026)
Gumeng Village, Bungah District, Gresik Regency has considerable fishery potential, especially Laosan fish, which has been more marketed in the form of fresh fish so that the economic added value is still limited. This community service program aims to increase the knowledge and skills of the community in developing processed laosan fish products that have added value. The activity was carried out through the delivery of materials, demonstrations, direct practices, interactive discussions, and product evaluations by involving Family Welfare Empowerment women and micro, small, and medium business actors in Gumeng Village. Participants were guided in the process of processing laosan fish into nuggets, shredded meat, and otak-otak and were given an understanding of the right processing techniques to produce quality products. The implementation of the activity went smoothly, and participants actively participated by participating in each stage of practice, asking questions, and providing input during the product tasting session. This program shows that product diversification is able to increase the added value of Laosan fish while strengthening the community's capacity to develop processed products that are more innovative and competitive so that it has the potential to support the development of micro, small, and medium enterprises in Gumeng Village.